2017
DOI: 10.1097/qad.0000000000001584
|View full text |Cite
|
Sign up to set email alerts
|

The effect of school attendance and school dropout on incident HIV and HSV-2 among young women in rural South Africa enrolled in HPTN 068

Abstract: Objective To estimate the association between school attendance, school dropout, and risk of incident HIV and HSV-2 infection among young women. Design We used longitudinal data from a randomized controlled trial in rural Mpumalanga province, South Africa, to assess the association between school days attended, school dropout and incident HIV and HSV-2 in young women aged 13–23 years. Methods We examined inverse probability of exposure weighted survival curves and used them to calculate 1.5, 2.5 and 3.5-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 44 publications
9
61
0
Order By: Relevance
“…This finding is similar to trends observed in some, but not all, sub-Saharan African countries [ 33 ]. Studies among young women in the general population have shown that staying in school can reduce HIV risk in some settings [ 34 , 35 ] and that educational attainment has a protective effect against HIV [ 36 , 37 ]. Low educational attainment has also been shown to be associated with initiating selling sex, likely contributing to increased HIV risk [ 5 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to trends observed in some, but not all, sub-Saharan African countries [ 33 ]. Studies among young women in the general population have shown that staying in school can reduce HIV risk in some settings [ 34 , 35 ] and that educational attainment has a protective effect against HIV [ 36 , 37 ]. Low educational attainment has also been shown to be associated with initiating selling sex, likely contributing to increased HIV risk [ 5 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Failure to remain in school is a strong predictor of adverse sexual health outcomes, with less educated women being at a higher risk for HIV and early pregnancy. Conversely, education, including both increased level of education [ 58 64 ] and school enrolment among adolescent girls, has been shown to prevent HIV infection [ 22 , 65 – 68 ]. This may be because schools create a ‘safe space’ and occupy women's time, such that young women have fewer older partners, fewer partners overall and safer sexual behaviour [ 69 , 70 ].…”
Section: Structural and Community Factorsmentioning
confidence: 99%
“…Furthermore, risk assessment tools for adolescents should consider context specific factors in addition to age, gender, and developmentally appropriate factors. For example, research has demonstrated the protective effect of schooling on HIV risk (and risk associated with dropping out of school), especially among adolescent girls in rural contexts . Furthermore, research among adolescent girls and young women in this context has shown that having older partners and engaging transactional sex are predictive of HIV incidence.…”
Section: Resultsmentioning
confidence: 99%